TA31: The Early Prehistory of Fiji - Clark, Geoffrey (Terra Australis, 2009)
I enjoyed reading this volume. It is rare to see such a comprehensive report on hard data published these days, especially one so insightfully contextualised by the editors' introductory and concluding chapters. These scholars and the others involved in the work really know their stuff, and it shows. The editors connect the preoccupations of Pacific archaeologists with those of their colleagues working in other island regions and on "big questions" of colonisation, migration, interaction and patterns and processes of cultural change in hitherto-uninhabited environments. These sorts of outward-looking, big-picture contextual studies are invaluable, but all too often are missing from locally- and regionally-oriented writing, very much to its detriment. In sum, the work strongly advances our understanding of the early prehistory of Fiji through its well-integrated combination of original research and the reinterpretation of existing knowledge in the context of wider theoretical and historical concerns. In doing so The Early Prehistory of Fiji makes a truly substantial contribution to Pacific and archaeological scholarship.